Documenting the heritage along the Silk Road: An ethnobotanical study of medicinal teas used in Southern Xinjiang, China. (5th October 2020) - Abdusalam, Aysajan; Zhang, Yu; Abudoushalamu, Maliyamu; Maitusun, Patiguli; Whitney, Cory; Yang, Xue-fei; Fu, Yao
Abstract: Ethnopharmacological relevance: People in Southern Xinjiang, China have been consuming medicinal teas for healthcare since before the ancient Silk Road markets began. Several pharmaceutical studies have illustrated the potential healthcare benefits of medicinal teas used in Southern Xinjiang, China. However, little information is available from the literature about the diversity of the species used and related traditional knowledge of these medicinal teas. Aims of the study: (i) create a comprehensive record of medicinal tea plant species (MTPS) and combinations used with related traditional knowledge for healthcare in Southern Xinjiang, China; (ii) assess safety of MTPS, and (iii) address conservation status for sustainable use of MTPS. Materials and methods: We employed both field and market surveys from 2014 to 2019 in 10 counties/cities and four main medicinal tea markets by using semi-structured interviews. We interviewed 236 informants and 70 medicinal tea shop vendors. The commonly used MTPS were ranked by Frequency of Citation. Safety issues were assessed based on expert knowledge and with reference to the official list of Medicinal Plants Used as Food. Conservation implications of plant use were assessed as part of the interviews and this was cross referenced with official records. Results: The surveys revealed 145 different plants from 65 families used for making medicinal teas, expanding the list of known Chinese herbal tea species from 782 to 884. Leguminosae, Rosaceae, Lamiaceae and Apiaceae were dominant families. Herbs (60.7%, 88 species) were the most commonly used plant types; fruits (23.1%, 50 species) and seeds (22.2%, 48 species) were commonly used parts. Nearly half (42.1%) of the plant species were introduced from abroad. Respondents reported more than 50 types of healthcare uses of medicinal teas. Tonic (13.7%, 71 species) and promoting digestion (9.6%, 50 species) were the most frequently mentioned healthcare uses. The majority of commonly used plant species were spices (20 species, 50%) and aromatic plants (10 species, 25%). Cinnamomum cassia (L.) J.Presl, Piper longum L. Syzygium aromaticum (L.) Merr. & L. M. Perry and Gardenia jasminoides J. Ellis were the most cited species. High doses of Piper longum L., Crocus sativus L., Curcuma longa L, and Senna alexandrina Mill. May have negative health implications. Assessments of conservation status and sustainable use of tea species indicate that wild harvesting of Nardostachys jatamansi (D. Don) DC. and Pterocarpus indicus Willd. Should be controlled and cultivation technologies should be improved. Conclusions: We found high plant species diversity and rich traditional knowledge of medicinal teas used in Southern Xinjiang, China. The traditional healthcare uses of some of the medicinal teas are also supported by pharmaceutical evidence. Others should be investigated further. Conservation pressures exist for commonly used wild species. China's 'Healthy China 2030' policy should do more to take traditional cultural practices into account. In doing so, both local and national government agendas may seek to promote sustainable harvest and to protect traditional knowledge so that this cultural heritage continues to serve human well-being into the future. Graphical abstract: Image 1